Falta de control en la posesión efectiva en los bienes muebles del causante ante notario público - Muñoz Delgado, Silvana Jercelita (2017)
The research work has as objective to analyze the lack of control that exists at the time when one or more heirs request the effective possession of property before a public notary. This problem happens when a person dies without leaving a will and to access the property of the causing, the heirs have to perform the process of effective possession of hereditary property before a Public Notary, however not always people who go before the public notary show the quality of heir, or they are not the only ones that exist, this given to the facility with which they can concur before a notary and to demonstrate effectively the relation of kinship with the causing, the same that have to be based on the expressed by the applicants with respect to the amount of heirs of the causing and not being able to verify what was manifested by not having an effective tool……